Studying local government's performance of Taft, Eastern Samar - Aserit, Evangeline C. (2007)
In view of the recent interest of many sectors to assess how various entities contribute to the promotion of public interest, the formulation of indicators of governance both timely and appropriate. This research is thus an attempt to take this effort a step further by focusing on the Minimum Basic Needs approach and how MBN indicators can enhance the assessment of governance (Bautista, 2002, 124).
To enhance the implementation of the Minimum Basic Needs approach, the Community-Based Poverty Indicators Monitoring System (CBPIMS) was jointly undertaken by the NEDA and NSO in 1997. Conducted purposely to improve data collection and processing of MBN (NSO, 1999), this project became part of the UNDP entitled "Strengthening Institutional Mechanisms for Convergence to Poverty Alleviation Efforts". It was expected to come out with revised data collection and processing instruments and capability building programs in pilot provinces designed to harness these innovations (MBN-CBPIMS Terminal Report Manila NSO, 1999).
Minimum Basic Needs derives from the evaluation of the community residents who are the direct beneficiaries of the services and management processes undertaken by the development managers, both from the government and the private sector (Bautista, 2002, 56).
MBN information, if regularly collected, ensures a longitudinal review of the performance of a locality.
MBN information, if regularly collected, ensures a longitudinal review of the performance of a locality.
MBN data gathering process relies on the involvement of component of the community and is therefore less expensive than applying one that makes use of paid workers.
MBN embodies a set of indicators that addresses basic requirements for survival, security and enabling needs to facilitate the attainment of quality of life. These indicators were not only designed by technical people from the national government but were also validated nationwide. They can be disaggregated to depict process, output, short-term effects and impact (Bautista, 2002, 212).
In addition, the public members are important in the processing, analyzing and in the planning tasks. Thus, this interface in development management can ensure sustainability, as citizens are involved in defining services that are delivered to them.
In this study, the evaluation of performance of said municipality took into account their MBN program, the budget allocated to that effect, local ordinances and resolutions enacted to make the program effective and efficient.
Undergraduate thesis (BASS Political Science) -- University of the Philippines, Tacloban.